Evaluating the concept of racial Fordism: a case study of the South African paper industry - Bethlehem, Lael Irene (My University, 2016)
This study seeks to evaluate Stephen Gelb's notion of racial Fordism as a theory of industrialisation in South Africa. The central concern of this study is to assess whether , racial Fordism provides a useful basis for understanding the development of industry. ) . ',r 'rue v~jdity of racial Fordism is analysed through a discussion of the conceptual §ttcllgth of the theory, as well as! through the application of the concept to a case study., .i) A review of t~~\~'literature on Fordism st.ows that Gelb's concept is based on '~~ I Jpietz's version of regulation theory, and especially his theory of Global Fordism, (\ Gelb's work is based on a reading of UJIl!ll~farznd rests on the assumption that"S:ouili 1\ Africa's patilioflindustriaUsation ls similar to the experience of Western)l economies such \ as the US:4~># whose path of development can be described as Ferdlsm, A'bboughilGelb qualifies the theory to take account of the specifics of the South African experience, he argues that the defining features of South African Industrialisation can be understood in terms of the theory .of Fordism, fit response, I argue that in addition to certain conceptual problems with the notion of racial Fordisrn, the concept is of limited value in explainmg the development of the pn1p and paper industry which serves as a case study for this dissertation. The evidence provided by the case study suggests that the theory of racial Fordism is insensitive to a " '\ \"1 number of key factors H1l1lcludingthe importance of the -ra. material base, the detenniDa1~v~of productivity, the role of the competitive regime and the t rt'il~dgesbetween marl;\Uacruring and other economic sectors. In addition, racial Fordlsm provides an inadequate analysis .of the nature of the domestic consumptlcn matket, the impact of racial domination on production and the role of the state, All of these factors are ,)1 important in explaining the development of the pulp and paper sector, Their absence in the theory of racial Fordism suggests that the concept has important limitations. Given the llmitatious of racial Fordism I argue that alternative conceptualisations need to he considered. E~ ahls light, Alice Amsdetl~s notion of tl~\~eindtWtriEili5ation' is examined. I conclude that this cenceptprovidea a useful basis from which to approach rut analysis of the process of imJustri~is~~on in SOl\l\thAfri.ea
A dissertation submitted to the Faculty of Arts at the University of the Witwatersrand, Johannesburg for the degree of Master of Arts.